2004
DOI: 10.1099/ijs.0.63109-0
|View full text |Cite
|
Sign up to set email alerts
|

Rubrobacter taiwanensis sp. nov., a novel thermophilic, radiation-resistant species isolated from hot springs

Abstract: Two novel bacteria, with an optimum growth temperature of approximately 60 6C, were isolated from Lu-shan hot springs in the central region of Taiwan. These isolates were aerobic, thermophilic, halotolerant, pink-pigmented, heterotrophic and resistant to gamma-radiation. Both pleomorphic, short, rod-shaped cells and coccoid cells were observed. Strains LS-286 (=ATCC BAA-452=BCRC 17198) and LS-293 T (=ATCC BAA-406 T =BCRC 17173 T ) represented a novel species of the genus Rubrobacter, according to a phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 36 publications
(41 reference statements)
2
45
1
1
Order By: Relevance
“…The bacteria of the genus Rubrobacter represent the most ancient lineage of the phylum Actinobacteria (High G + C Gram-positive bacteria) known and are assigned to three known species, namely R. radiotolerans, R. taiwanensis and R. xylanophilus with optimum growth temperatures of 45, 55, and 60°C, respectively (Carreto et al 1996;Chen et al 2004;Suzuki et al 1988). All strains examined of Rubrobacter are gamma-radiation resistant and R. xylanophilus is, not only the most thermophilic actinobacterium known, but also the only true extremely radiation-resistant thermophile (Suzuki et al 1988;Ferreira et al 1999;Chen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteria of the genus Rubrobacter represent the most ancient lineage of the phylum Actinobacteria (High G + C Gram-positive bacteria) known and are assigned to three known species, namely R. radiotolerans, R. taiwanensis and R. xylanophilus with optimum growth temperatures of 45, 55, and 60°C, respectively (Carreto et al 1996;Chen et al 2004;Suzuki et al 1988). All strains examined of Rubrobacter are gamma-radiation resistant and R. xylanophilus is, not only the most thermophilic actinobacterium known, but also the only true extremely radiation-resistant thermophile (Suzuki et al 1988;Ferreira et al 1999;Chen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…All strains examined of Rubrobacter are gamma-radiation resistant and R. xylanophilus is, not only the most thermophilic actinobacterium known, but also the only true extremely radiation-resistant thermophile (Suzuki et al 1988;Ferreira et al 1999;Chen et al 2004). R. xylanophilus is also halotolerant growing in medium containing up to 6% NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…These are all aerobic heterotrophs. The few other members of this subclass are aquatic thermophiles of the genera Rubrobacter and Thermoleophilum (19,21,106,117). Overall, there are many lineages without cultured representatives in all three subclasses of soil-inhabiting actinobacteria, especially in the subclasses Rubrobacteridae and Acidimicrobidae, but also some in the subclass Actinobacteridae (e.g., see references 5, 50, 54, 73, 79, 89, and 90).…”
Section: Phylum Level Diversitymentioning
confidence: 99%
“…Several , mg/g clones from this study are related to Rubrobacter species with a 94-95% sequence similarity. Rubrobacter have been isolated both in soils and thermal waters [Carreto et al, 1996;Chen et al, 2004;Saul et al, 2005;Suzuki et al, 1988], and Rubrobacter species have been found to be widespread in arid Australian soils [Holmes et al, 2000] and arid Antarctic soils [Aislabie et al, 2006]. The most well studied Rubrobacter species is radiotolerans with an ability to survive a 25kGy dose of radiation [Ferreira et al, 1999].…”
Section: Colony Forming Units (Cfu)mentioning
confidence: 99%